Pengaruh Social Media Marketing, Consumer Engagement dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk di Gudang Kosmetik Purwokerto - Nadzirotus Salmah; Meydy Fauzriridwan; Herni Justiana Astuti; Fatmah Bagis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The purpose of this research is to determine the influence of social media marketing, consumer engagement, and service quality on the purchase decisions for products at Gudang Kosmetik Purwokerto. The population in this study is the customers of Gudang Kosmetik Purwokerto (GKP). The sample in this study consists of 118 respondents who are customers of Gudang Kosmetik Purwokerto. The sampling technique used in this study is purposive sampling, with the criteria of having purchased at Gudang Kosmetik Purwokerto (GKP) more than two times. The data analysis used is Smart-PLS 3.0. The results of this study show that 1) Social media marketing has a positive and significant effect on purchase decisions for products at Gudang Kosmetik Purwokerto, 2) Consumer engagement has no effect on purchase decisions for products at Gudang Kosmetik Purwokerto, and 3) Service quality has no effect on purchase decisions for products at Gudang Kosmetik Purwokerto. The implication for Gudang Kosmetik Purwokerto is that management must prioritize improving service quality and the effectiveness of social media content as the main drivers of purchase decisions.